A progress on the shifted power function for modeling informetric laws - Ye, Fred Y; Ye, Fred Y. (Malaysian Journal of Library and Information Science, 2017)
Fred, Y. Y. (2014). A progress on the shifted power function for modeling informetric laws. Malaysian Journal of Library & Information Science, Vol.19, no. 1: 1-15. Based on three theorems for size-to-rank transformations, the shifted power function is used to set up a theoretical framework unifying informetric distributions. While the shifted power function with time-type exponential cutoff supplies a unifying informetric framework, the shifted power function with space-type exponential cutoff can be linked to the Pareto and Weibull distributions. The exponent is the crucial parameter in a power function, determining the most important characteristics of the power-law distribution.